Vadamarga As A Classical Research Tool In Ayurveda Samhitas: A Critical Review - Kumar, Niraj; Day, Harnarayan; Mishra, Satendra Kumar (Journal of Neonatal Surgery, 2025)
Ayurveda, the ancient Indian system of holistic health, is not merely a therapeutic science but a comprehensive knowledge tradition rooted in rigorous epistemology and rational inquiry. Among its many intellectual tools, Vadamarga—the pathway of discourse and debate—emerges as a profound classical research methodology. Rooted in texts such as Charaka Samhita, Sushruta Samhita, and Nyaya Darshana, Vadamarga systematizes knowledge validation through structured argumentation, logical reasoning (Tarka), valid proof (Pramana), and dialectical exchange (Vadakatha).This review critically examines the theoretical foundation and practical relevance of Vadamarga in the Ayurvedic corpus. It explores its three primary forms—Vadha, Jalpa, and Vitanda—as well as the roles of prashnaka (questioner), prativadi (respondent), and madhyastha (moderator). These mechanisms ensured not only the transmission of knowledge but also its continual refinement through public dialogue and critical evaluation.By comparing these ancient deliberative practices with modern research protocols like hypothesis testing, clinical trials, and peer-reviewed publication, the paper positions Vadamarga as a precursor to evidence-based medicine. It also discusses how the reintroduction of Vadamarga into current Ayurvedic research and education can enhance analytical rigor, promote ethical debate, and improve the quality of clinical documentation.The integration of classical methods like Vadamarga with modern tools presents a pathway toward strengthening Ayurveda’s credibility in the global medical community while remaining true to its epistemological roots